Spiritual Warfare and the Church's Mission According to Ephesians 6:10-17 - Mark D. Owens (Tyndale Bulletin, 2016)
Ephesians 6:10-17 is typically understood as either a call to engage in spiritual warfare with the ‘powers’ or as a plea for ethical living. While these two interpretations are not necessarily incorrect, they are likely incomplete. More specifically, they do not account for the author’s use of Isaiah in verses 14-15 and 17 and how this text summarises the whole of Ephesians. When one considers these two factors, it becomes reasonable to conclude that this text portrays the church as a community of ‘divine-warriors’ who continue Christ’s mission by extending the new creation inaugurated by His sacrificial death and resurrection.